EVALUASI PROGRAM HOMESCHOOLING GROUP UNTUK ANAK USIA 5-6 TAHUN - CHOIRIYAH, CHOIRIYAH (Program Studi Magister Pendidikan Anak Usia Dini, 2015)
Abstract: The research objective was to evaluate the Homeschooling Program Group 5-6 Year Olds in Khairu Ummah Bekasi Jatisampurna 2014. Research program evaluation apply Cippo models that include context, input, process and output products. The research was conducted for two months ie from May to June 2014. The results showed: (1) aspects of the context, the implementation of the program of homeschooling services group operating license is not obtained in the form of an operating license homeschooling group, but only in the form of an operating license for CLC (Community Learning Center ) issued by the Director General of PLS, (2) aspects of input show that Homeschooling Group Khairu Ummah Jatisampurna-Bekasi mostly categorized as good, (3) aspects of the process, Homeschooling Group Khairu Ummah Jatisampurna-Bekasi mostly categorized as good, (4) aspects of the product, showing that Homeschooling Group Khairu Jatisampurna Ummah Bekasi partly categorized as good, and (5) Outcomes aspect, shows that homeschool graduates Jatisampurna Group Khairu Ummah Bekasi who continue to pursue formal basic education was considered successful because students achieve the learning objectives in elementary formal fine. Keywords: EvaluationmodelsCIPPO, HomeschoolingGroup, ECD